Estudo da entidade sindical de primeiro grau no contexto da liberdade sindical no Brasil: um perfil da atuação de sindicatos da categoria profissional, no município de Fortaleza, no período de 2010 a 2012 - Farias, Regina Sonia Costa (2013)
Study of the union entity in the context of freedom of association in Brazil: a profile of the activities of trade unions in the professional category, in Fortaleza, concerning the period from 2010 to 2012. Aims to profile the performance of the union entity, headquartered in Ceará’s capital, in that time span. Specifically, analyses the representation in the workplace, describes the health care services provided to its members, identifies the sources of funding used by the union, knowing its actions in defense of the category and the dialogue between the union and its base. The methodology was one of investigative and descriptive nature. It was a field research, of the participant type, whose data were collected through a separate instrument, previously developed by the researcher and applied directly to a member of the executive board of the union. The results led to the following main conclusions: a. representation in the workplace is given by the representative of the employees in the company and the union leader b. unions are supported by the contributions recognized by Brazilian law c. the union actions in defense of the workers happens through participation in the collective bargaining process and the outbreak of the strike d. the communication with the union base is through campaign for unionization, union mobilization and visits to the workers it represents.